A 5-year review of anaesthetic techniques for caesarean section in parturients with heart diseases - Anuar, Norhayati (2018)
Background : Parturients with heart diseases that presents for delivery possess challenges to anaesthetists, cardiologists and obstetricians. The objectives of study are to study the prevalence and characteristics of parturients underwent Caesarean section in Hospital Serdang. Methods : This is a retrospective study where the data for five years was collected in Hospital Serdang between 1st January 2011 till 31st December 2015. Data of the cases selected was retrieved from the computerized patient data system which is the electronic data bases, Lab Information System (LIS) via Medicomm and E His Live of Hospital Serdang, Selangor. Demographic, types of anaesthesia and postoperative care were recorded. Results : The descriptive methods and multiple logistic regression were applied to answer the objectives of the study. Total of 84 parturients involved in this study. Multiple logistic regression analysis showed that no factor was significantly associated with parturients with heart diseases that underwent Caesarean section under regional anaesthesia that underwent Caesarean section in Hospital Serdang. The proportion of parturients underwent Caesarean section using regional anesthesia was 89.3% (95% CI: 83.3, 95.3). Mean age of them was 30.9 (5.38) years old. Meanwhile, mean (SD) parity and gestational weeks were 1.6 (0.87) and 36.9 (1.42) weeks, respectively. Conclusion : However based on descriptive analysis, it was found that regional anaesthesia is still the most preferable techniques for Caesarean section among parturients with severe heart conditions